Advanced metalcutting calculators - Isokov, Edmund
Advanced metalcutting calculators contains four calculators for major metalcutting operations: milling, turning, boring, drilling; and a fifth for calculating exact machining time when facing, cutting off, and deep grooving. All calculators are developed in Microsoft Excel and execute all parameters in both U.S. and metric units. These calculators provide computational results more accurate than any other calculators on the market and can be used by anyone involved in manufacturing, including machinists, technicians and engineers.